Flexible double-cross-linked cellulose-based hydrogel and aerogel membrane for supercapacitor separator. Issue 47 (21st November 2018) - Li, Liyuan; Lu, Feixue; Wang, Chao; Zhang, Fengling; Liang, Weihua; Kuga, Shigenori; Dong, Zhichao; Zhao, Yang; Huang, Yong; Wu, Min
Abstract : A cellulose-based flexible double-cross-linked hydrogel with hierarchical porosity (max. 80%) was obtained by a facile solution-phase method by using polydopamine (PDA) as a crosslinker between cellulose and polyacrylamide (PAM). Abstract : A cellulose-based flexible double-cross-linked hydrogel with hierarchical porosity (max. 80%) was obtained by a facile solution-phase method by using polydopamine (PDA) as a crosslinker between cellulose and polyacrylamide (PAM). The investigation on the ratio of dopamine/acrylamide (DA/AM) reveals that the π–π stacking of the catechol groups in PDA and the abundant hydrogen bonds distributed in the gel network exert key effects on the hydrogels' mechanical properties. At the premium ratio of 0.4 (C4 -DM-40), the mechanical and self-healing properties of the hydrogel are superior to those of other hydrogels. Fe 3+ -functionalizing endows the hydrogel with enhanced conductivity and sensitivity, as evidenced by the 3-fold increase in resistance variation (Δ R / R 0 ) in a finger-bending monitoring test. An electric double layer supercapacitor using the KOH-saturated C4 -DM-40 aerogel membrane as a polymer electrolyte presents high capacitance of 172 F g −1 at 1.0 A g −1 and long cycling life of 10 000 cycles with 84.7% capacitance retention due to electrolyte retention of 548.6%. Remarkably, an integrated micro-supercapacitor is fabricated by directly depositing activated carbon materials onto the C4 -DM-40 hydrogel membrane. The device shows areal capacitance of 275.8 mF cm −2 and volumetric capacitance of 394.1 F cm −3 at 10 mV s −1 . These findings suggest that the multi-functional cellulose-based hydrogels reported in this study display various potentials for practical applications not only in human health monitoring but also in portable and energy-storage devices.